Factors Influencing Climate Information Access of the Farmers in Hiran Region, Somalia - Odawa, Abdiwali; Mucheru-Muna, Monicah; Mburu, Benson; Omari, Erick (International Journal of Environmental Sciences, 2024)
Purpose: Like other poor states and post-conflict countries, Somalia faces significant challenges in achieving the SDGs, particularly concerning food security. Because agricultural productivity is compromised, it immediately and significantly jeopardizes the nation's food security. Adapting to climate change can maximize its benefits and lessen many of its horrendous side effects. However, Somalia does not address or cover farmers' access to climatic information, which is important when organizing policy responses. This study's goal was to assess the variables that affect farmers in Somalia's Hiran region's ability to obtain climate information. Methodology: The target population of this study was smallholder farmers in the Hiran region, particularly in the Baladweyn and Bulaburte districts. Both purposive and random sampling were utilized. A questionnaire was used to gather data from 222 randomly chosen smallholder farmers as part of a survey research design. Descriptive statistics and binary logistic regression were used to test the data using STATA and SPSS. The data was presented using tables and figures. Findings: Most farmers (78%) had access to climate information. The most common sources of information on climate crises were radio (95%), agricultural extension agents (80%), and firsthand observation (75%). Gender (p = 0.020), marital status (p = 0.036), education level (p = 0.047), farm size (p = 0.000), distance to the market (p = 0.000), and support from local and international agencies (p = 0.013) had a significant correlation with farmers access to climate information. The report advised Somalia's federal government and regional and foreign non-governmental organizations to proceed with intervention plans, focusing particularly on variables that were identified. Unique Contribution to Theory, Practice, and Policy: Study outcomes contribute significant information to policymakers, professionals, and the federal government of Somalia to develop policies and regulations that are relevant to the farmer's needs to adapt to the negative impacts of climate crises. It will also lead to necessary coordination among different climate actors, stakeholders, and farming communities in the region to fill any climate information gap. This will finally allow farmers to access well-timed and dependable information regarding climate disasters.